2012
DOI: 10.1111/j.1600-0706.2012.19952.x
|View full text |Cite
|
Sign up to set email alerts
|

Temperature indirectly affects benthic microalgal diversity by altering effects of top–down but not bottom–up control

Abstract: Understanding the ecological mechanisms that underlie species diversity decline in response to environmental change has become an urgent objective in current ecological research. Not only direct (lethal) effects on single species but also indirect effects altering biotic interactions between species within and across trophic levels comprise the driving force of ecosystem change. In an experimental marine benthic microalgae–grazer system we tested for indirect effects of moderate temperature change on algal div… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 47 publications
0
14
0
Order By: Relevance
“…Disparities in responses may be due in part to differences in background levels of nutrients that occur among ecosystems, with peatlands typically among the most nutrient deplete (Wieder 2006). Additionally, the magnitude of warming in studies reporting an increase in algal metabolism was slightly more elevated than temperatures observed in the present study (e.g., Baulch et al 2005;Demars et al 2011), while studies evaluating a similar temperature increase found only small changes in algal production (Werner and Matthiessen 2013). A combination of warming and nutrient enrichment did, however, have a synergistic effect on algal metabolism, indicating that even minimum warming will further accelerate the effects of nutrient enrichment on algal production.…”
Section: Discussionmentioning
confidence: 46%
“…Disparities in responses may be due in part to differences in background levels of nutrients that occur among ecosystems, with peatlands typically among the most nutrient deplete (Wieder 2006). Additionally, the magnitude of warming in studies reporting an increase in algal metabolism was slightly more elevated than temperatures observed in the present study (e.g., Baulch et al 2005;Demars et al 2011), while studies evaluating a similar temperature increase found only small changes in algal production (Werner and Matthiessen 2013). A combination of warming and nutrient enrichment did, however, have a synergistic effect on algal metabolism, indicating that even minimum warming will further accelerate the effects of nutrient enrichment on algal production.…”
Section: Discussionmentioning
confidence: 46%
“…Grazers may facilitate macroalgal growth either by removing fouling epiphytes or by increasing the concentration of available nutrients (Guidone et al 2012). The context-dependency of facilitation in our study may be explained by the more pronounced effect of grazers on nutrient concentrations at elevated temperatures (Werner and Matthiessen 2013) or the greater potential for grazing to alleviate the growth-inhibiting effects of heavier epiphytic loads that develop under conditions of reduced wave action and warming (Kersen et al 2011). The apparent disruptive effect of wave action on warming-induced positive species interactions is another means by which altered environmental conditions can modify the effects of consumer diversity change.…”
Section: Discussionmentioning
confidence: 68%
“…In most vegetated coastal ecosystems, algal-feeding mesograzers play a key role in controlling ephemeral algae biomass, thereby facilitating habitat-forming perennial macrovegetation, such as the eelgrass Z. marina (39,40). Suppression or removal of mesograzers, for example, by trophic cascades induced by overfishing of large predators, can flip these ecosystems to bottom-up stimulation (11,12,39,40). We observed this same pattern; mesograzers affected the balance between bottom-up and top-down regulation by (i) feeding on epiphytic and floating macroalgae, leading to increased light penetration; and (ii) preying upon smaller sediment-associated fauna that in turn fed on the benthic microalgae.…”
Section: Discussionmentioning
confidence: 99%
“…For example, efficient herbivores such as muskoxen and caribou dampen the effects of warming on plant communities on the arctic tundra (10). In contrast, predation on herbivores augments the effects of warming on plants by shifting the control of shallow-water aquatic food webs from top-down to bottom-up (11)(12)(13).…”
mentioning
confidence: 99%